PEMBERDAYAAN ANGGOTA AISYIYAH WILAYAH DIY MELALUI PROGRAM CERDAS LINGKUNGAN DALAM PEMANFAATAN LAHAN SEMPIT - Indra Putra, Ichsan luqmana (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Population increase will be accompanied by increasing in cloth, food and shelter. This increase causes the green area and urban yard narrowed. Plants that can be planted at the yard only certain and usually potted plants. Responding to this, the Biology Study Program, FMIPA, UAD in collaboration with the Environmental and Disaster Management Agency (LLHPB), PWA DIY formulated a farming solution. The purpose of this activity were to increase the knowledge about environmental damage and knowledge of hydroponics, benefits, and types of PWA DIY members. As well as improving the skills to cultivate through hydroponics. The methods that used were counseling and training. Planting process through DFT (Drip Flow Technique) and Wick systems with used bottles. The DFT installation used as a pilot project at the PWA DIY office, while the Wick System installation was taught at every opportunity. The results that obtained are PWA DIY members had carried out the harvesting once in the DFT installation. Vegetables that harvested were pakcoy and salada. The conclusion of this activity were the use of hydroponics can help utilize and maximize narrow land in urban areas. The use of hydroponic systems was more effective and efficient than the use of pots.